Brussels court ruling on tracking-based ads a major win for right to privacy - Amnesty International (Amnesty International, 2025)
On 14 May the Brussels Court of Appeal ruled that the consent model used by the tracking based online advertising industry is illegal under EU privacy law. The ruling establishes that the Transparency and Consent Framework fails to meet GDPR requirements for user consent and transparency.